Geo-Congress 2020. selected papers from sessions of Geo-Congress 2020 : February 25-28, 2020, Minneapolis, Minnesota - Kavazanjian, Edward; Hambleton, James P.; Makhnenko, Roman; Budge, Aaron S. 1974- (American Society of Civil Engineers, 2020)
Selected papers from sessions of Geo-Congress 2020, held in Minneapolis, Minnesota, February 25-28, 2020. Sponsored by the Geo-Institute of ASCE. This Geotechnical Special Publication contains 36 peer-reviewed papers in the emerging field of biogeotechnical engineering. Topics include: bio-mediated geotechnics; bio-inspired geotechnics; ground improvement applications; microbially-induced calcite precipitation; and bio-mediated remediation of soil and groundwater. GSP 320 will provide current information to practitioners and researchers on the emerging field of biogeotechnics.
Keywords: Geotechnical engineering -- Congresses.; Bioengineering -- Congresses.; elektronické knihy; electronic books